Organic Vegetable Production - Danielle D. Treadwell (EDIS)
Revised! HS-720, an 18-page fact sheet by D.D. Treadwell, is a general introduction to organic production, replacing a 4-page article by J.M White. Includes links to additional information and references. Published by the UF Department of Horticultural Sciences as part of the Vegetable Production Guide for Florida, September 2006.